Global prevalence and contributing factors of nurse burnout: an umbrella review of systematic review and meta-analysis - Addisu Getie; Temesgen Ayenew; Baye Tsegaye Amlak; Mihretie Gedfew; Afework Edmealem; Worku Misganaw Kebede (BMC Nursing)
Abstract Introduction Nurse burnout negatively impacts patient care quality, safety, and outcomes, while harming nurses’ mental health, job satisfaction, and retention. It also imposes financial burdens on healthcare organizations through absenteeism, reduced productivity, and higher turnover costs, highlighting the need for research to address these challenges. The umbrella review methodology was selected to integrate evidence from multiple systematic reviews and meta-analyses, offering a broad and in-depth summary of existing research to guide practice and policy. This approach equips stakeholders with a holistic understanding of the multifaceted impacts of nurse burnout, facilitating the design of effective interventions that support nurses, enhance healthcare delivery, and optimize patient outcomes. Consequently, this umbrella review aims to evaluate the global prevalence and contributing factors of nurse burnout. Methods This umbrella review included 14 systematic reviews and meta-analyses identified from various databases. The quality of each study was assessed using the Assessment of Multiple Systematic Reviews (AMSTAR II). Data were extracted using Microsoft Excel and analyzed with STATA 17.0. Heterogeneity was measured using Higgin’s I2 Statistics, and summary prevalence estimates were calculated with the Der Simonian-Laird random-effects model. Meta-regression and subgroup analyses were conducted to identify the source of high heterogeneity. Publication bias was assessed using funnel plots and Egger’s regression test, with the former providing a visual assessment of bias and the latter offering a statistical method to detect asymmetry. Results The global prevalence of nurse burnout was evaluated in three areas: emotional exhaustion (33.45%, 95% CI 27.31–39.59), depersonalization (25.0%, 95% CI 17.17-33.00), and low personal accomplishment (33.49%, 95% CI 28.43–38.55). Emotional exhaustion was most common among nurses working during the COVID-19 pandemic (39.23%, 95% CI 16.22–94.68). Oncology nurses experienced the highest rate of depersonalization (42%, 95% CI 16.71–77.30), while nurses in intensive care units reported the highest rate of low personal accomplishment (46.02%, 95% CI 43.83–48.28). Conclusions Nurse burnout is prevalent worldwide, often marked by a sense of low personal accomplishment. Several factors contribute to this issue, including role conflict, negative emotions, family problems, moral distress, stress, commuting distance, predictability of work tasks, and workplace advancement.